A New Manuscript of More's English Works. (23rd February 2019) - Edwards, A S G; Fraas, Mitch
Abstract: This note describes the various recent sales of separate leaves from a manuscript containing several of Thomas More's English works: The Answer to the Poisoned Book; The Confutation of Tyndale's Answer; and A Dialogue Concerning Heresies . It comments on the odd circumstances of the dispersal of these leaves.